Vegetation and soil responses to concrete grinding residue application on highway roadsides of eastern nebraska - Wingeyer, Ana Beatriz (2018)
As a precautionary principle, the National Pollutant Discharge Elimination System (NPDES) permit establishes that the primary pollutant in concrete grinding residue (CGR) is its alkalinity and restricts CGR roadside discharge to 11 Mg ha-1 or the agronomic liming rate, whichever is lower. We evaluated the effect of CGR application on roadside soil chemical properties, existing vegetation, and rainfall runoff. Five CGR rates (0, 11, 22, 45, and 90 dry Mg ha-1) were tested on roadsides slopes at two different locations in eastern Nebraska. Vegetation, soil, and runoff characteristics were evaluated before CGR application and 30 d and 1 yr after CGR application. Soil pH of control plots averaged 8.3 and 8.5 for each site respectively, across depths and slope positions, thus not requiring any liming for agronomic purposes. Soil electrical conductivity (EC, 1:1) averages of control plots were 0.79 and 1.24 dS m-1 across depths and slope positions. In the short term (30 d) the highest CGR application affected the 0- to 7.5-cm soil depth by increasing soil extractable Ca (21 and 25% for each site, respectively), soil pH (0.2, south site), and soil EC (0.2 dS m-1) compared with the control. However, these changes in soil did not persist 1 yr after CGR application. The pH buffering capacity of soil prevented post-CGR-application pH from exceeding 8.9, even at the highest application rate. Application of CGR did not produce any differences in biomass production, botanical composition, and runoff characteristics at either site. From our study, CGR up to ~90 dry Mg ha-1-about the amount produced during diamond grinding operations-can be one-time applied to roadside soils of similar characteristics on already established vegetation.